Eksplorasi Pengalaman Wisatawan Pada Tahapan Visitor Journey Di Monumen Nasional, Jakarta - Cheryl Jesslyn Waisa; Wiwik Sari (Journal of Innovation Research and Knowledge, 2026)
The development of digital technology has transformed the way tourists obtain information and shape their expectations before undertaking a trip. Tourist experiences are not only formed while visitors are at the destination but also begin before the visit and continue after the trip has ended. As one of Indonesia's leading historical tourism destinations, the National Monument (Monas) still faces challenges in delivering visitor experiences that meet tourists' expectations. Therefore, this study aims to explore tourists' experiences at the National Monument, Jakarta, by adopting the visitor journey approach, which consists of the pre-visit, during visit, and post-visit stages. This study employed a qualitative approach using purposive sampling to select participants. The informants consisted of 30 tourists who had visited or were visiting the National Monument. Data were collected through semi-structured interviews, observations, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that tourists' experiences at the National Monument are formed throughout the three stages of the visitor journey. During the pre-visit stage, experiences begin with information searching and trip planning. During the during visit stage, tourists gain positive experiences through the destination's attractions, facilities, and overall atmosphere, although several challenges remain, such as long queues and limited supporting facilities. In the post-visit stage, most tourists expressed their intention to revisit the destination and share their experiences through social media or online review platforms.